Growth Kinetics and Mechanistic Action of Reactive Oxygen Species Released by Silver Nanoparticles from Aspergillus niger on Escherichia coli. (16th June 2014) - Ninganagouda, Shivaraj; Rathod, Vandana; Singh, Dattu; Hiremath, Jyoti; Singh, Ashish Kumar; Mathew, Jasmine; ul-Haq, Manzoor
Abstract : Silver Nanoparticles (AgNPs), the real silver bullet, are known to have good antibacterial properties against pathogenic microorganisms. In the present study AgNPs were prepared from extracellular filtrate of Aspergillus niger . Characterization of AgNPs by UV-Vis spectrum reveals specific surface plasmon resonance at peak 416 nm; TEM photographs revealed the size of the AgNPs to be 20–55 nm. Average diameter of the produced AgNPs was found to be 73 nm with a zeta potential that was −24 mV using Malvern Zetasizer. SEM micrographs showed AgNPs to be spherical with smooth morphology. EDS revealed the presence of pure metallic AgNPs along with carbon and oxygen signatures. Of the different concentrations (0, 2.5, 5, 10, and 15  μ g/mL) used 10  μ g/mL were sufficient to inhibit 10 7  CFU/mL of E. coli . ROS production was measured using DCFH-DA method and the the free radical generation effect of AgNPs on bacterial growth inhibition was investigated by ESR spectroscopy. This paper not only deals with the damage inflicted on microorganisms by AgNPs but also induces cell death through the production of ROS released by AgNPs and also growth kinetics of E. coli supplemented with AgNPs produced by A. niger .